"It's second best": A mixed-methods evaluation of the experiences and attitudes of people with musculoskeletal pain towards physiotherapist delivered telehealth during the COVID-19 pandemic. (April 2022) - Barton, C.J.; Ezzat, A.M.; Merolli, M.; Williams, C.M.; Haines, T.; Mehta, N.; Malliaras, P.
Abstract: Background: Musculoskeletal physiotherapy practice rapidly adopted telehealth during the COVID-19 pandemic, providing a unique opportunity to evaluate the experiences and attitudes of people who would not usually engage with these services. Methods: A sequential mixed-methods study recruited people with musculoskeletal pain conditions accessing Australian private practice physiotherapist services. Part 1 involved an online survey of telehealth services accessed, treatments and resources provided, self-reported global change in condition, and attitudes toward telehealth. Part 2 involved semi-structured interviews with a subset of survey participants, exploring experiences and attitudes towards telehealth. Quantitative data was reported descriptively. Qualitative data was evaluated using inductive thematic analysis. Results: 172 participants responded to the survey, and 19 were interviewed. 95% accessed video-based telehealth, and 85% reported condition improvement. 84% agreed it was an efficient use of their time, 75% agreed it was financially viable, and 73% agreed their condition was accurately diagnosed. 62% percent believed telehealth should be less expensive than in-person services. Qualitative analysis revealed four themes (17 subthemes), including (i) telehealth had value, but generally perceived as inferior to in-person care; (ii) challenges related to assessment, diagnosis, 'hands on' treatment, observation, communication, and technology; (iii) advantages to access safe, expert, and convenient care; and (iv) importance of supportive technology, including video and supplementary resources. Conclusion: Physiotherapist telehealth services provided to people with musculoskeletal pain during the pandemic was valued. However, telehealth was generally perceived as inferior to traditional in-person care, and may be best used as part of a hybrid model of care. Highlights: 85% of survey respondents accessing telehealth reported condition improvement. Telehealth was valued, but typically considered inferior to in-person care. 62% of survey respondents believed telehealth should be less expensive. Key challenges included lack of 'hands on' treatment and technology. Key benefits included access to safe, convenient, and expert care.